Expression profiling for bladder cancer: strategies to uncover prognostic factors. Issue 12 (December 2010) - Bartsch, Georg; Mitra, Anirban P; Cote, Richard J
Despite being a common cancer worldwide, management of transitional cell carcinoma of the bladder currently relies primarily on clinical staging and histopathologic parameters. Assaying alterations in molecular pathways can contribute valuable information that can accurately predict outcome and chemotherapeutic response in individual patients with bladder cancer. Medium- to high-throughput gene-expression profiling technologies are now allowing multiplexed assessment of alterations responsible for the genesis and progression of bladder tumors. These investigations employ global or pathway-based approaches to define molecular signatures that can predict prognosis independent of traditional clinical performance metrics. Prognostic panels generated using these strategies can also elucidate the biology of tumor progression and identify potential therapeutic targets.